La tesis de la conexión intrínseca entre derecho y moral: sus consecuencias para la ética profesional del abogado - Chávez-Fernández Postigo, José Carlos (Pontificia Universidad Católica del Perú, 2025)
Frequently, reflections on the legal philosophical conceptions of law are posited, at least implicitly, as independent from reflections on the ethics of the legal professions. However, this brief work aims to show that a central aspect that defines the nuances of such conceptions —specifically, the way in which the thesis of the necessary connection between law and morality is upheld— is essential for addressing practical consequences in the ethical or moral exercise of legal professions, particularly that of lawyers. Starting from the real or apparent tension between the lawyer's duty of «truthfulness and justice» and the duty of «diligence and confidentiality» when acting as a defense attorney in a criminal trial, this paper will defend the thesis that law and morality —without being identified or confused with one another— maintain an «intrinsic» relationship. This relationship allows for the compatibility of a lawyer's professional practice with these duties, while supporting the view that morality subordinates law, insofar as both are primarily practical or prescriptive reasoning-knowledge disciplines, rather than technical or instrumental ones, in Aristotelian terminology. This will lead to the conclusion that both judges and lawyers who participate in such legal proceedings are bound in their professional practice by a morality that can reasonably be considered objective, while acknowledging the unique implications of this connection for the lawyer's professional work.

Frecuentemente la reflexión sobre las concepciones iusfilosóficas acerca del Derecho se postulan, al menos implícitamente, como independientes de la reflexión sobre la ética de las profesiones jurídicas. Sin embargo, este breve trabajo pretende mostrar que un aspecto central que define los matices de dichas concepciones —en concreto: la forma de sostener la tesis de la conexión necesaria entre Derecho y moral— resulta imprescindible en orden a plantear consecuencias prácticas para el ejercicio ético o moral de las profesiones jurídicas y, en particular, la del abogado. A partir de la tensión real o aparente entre el deber de «veracidad y justicia», y el de «diligencia y reserva» del abogado que actúa como defensor en un proceso penal, este trabajo defenderá la tesis de que el Derecho y la moral —sin llegar a identificarse o confundirse— guardan una relación «intrínseca», la que permite compatibilizar el ejercicio profesional de los abogados respecto de los mencionados deberes, con la tesis de que la moral subordina al Derecho en tanto que ambas son disciplinar y normativamente razonamiento-conocimiento primordialmente práctico o prescriptivo, y no técnico o instrumental, en terminología aristotélica. Ello permitirá sostener que tanto el juez como el abogado que actúan en un proceso de tal naturaleza están vinculados en su ejercicio profesional por una moral que se postule razonablemente como objetiva, sin perjuicio de destacar las peculiaridades de dicha vinculación para el trabajo profesional del abogado.
The Thesis of the Intrinsic Connection Between Law and Morality: Its Consequences for the Professional Ethics of the Lawyer
Keywords: Legal philosophical conceptions; Law-morality connection; Professional ethics of the lawyer; Duty of truthfulness; Duty to serve justice; Duty of confidentiality; Duty of diligence; Concepciones iusfilosóficas; Conexión derecho-moral; Ética profesional del abogado; Deber de veracidad; Deber de servir a la justicia; Deber de reserva; Deber de diligencia; https://purl.org/pe-repo/ocde/ford#5.05.01